Efficacy of Cold Karman Cannulae in Reducing Pain During Office-Based Endometrial Biopsy: A Prospective Randomized Controlled Trial - Bulutlar, Eralp; Uluutku Bulutlar, Gizem Berfin (Gynecology Obstetrics & Reproductive Medicine, 2025)
Objective: The study aimed to evaluate the efficacy of cold Karman cannulae, stored at -17°C, in reducing pain levels during office-based endometrial biopsy procedures. Study Design: This prospective, randomized controlled trial was conducted between 2021 and 2022, involving 300 female patients aged 30-60, with abnormal uterine bleeding or increased endometrial thickness. Participants were randomly assigned to two groups: the experimental group, which used cold Karman cannulae (n=150), and the control group, which used room temperature cannulae (n=150). Pain levels were assessed using the Numeric Rating Scale (NRS) immediately after the procedure and ten minutes later. Results: The mean NRS pain score was significantly lower in the cold cannula group (4.70 ± 1.278) compared to the room temperature cannula group (6.27 ± 1.089) (p<0.05). No significant complications, such as cervical damage or infection, were observed in either group. The use of cold cannulae also facilitated the easier technical performance of the biopsy due to reduced cervical resistance. Conclusion: The application of cold Karman cannulae significantly reduces pain perception during office-based endometrial biopsy, making it a viable option for improving patient comfort and procedural efficiency. These findings support the integration of cold application techniques in gynecological procedures to enhance pain management.